Skip to main content

Theory and Modern Applications

Fredholm type integral equation in extended \(M_{b}\)-metric spaces


In this manuscript, we prove some new fixed point results for a self-mapping on extended \(M_{b}\)-metric spaces, under some new types of contractions, which generalizes many results in the literature. Also, we present some interesting examples to illustrate our work.

1 Introduction and preliminaries

Lately, fixed point theory has become the focus of many researchers and that is due to its applications in many fields, such as engineering and computer sciences. Also fixed point theory can be used to solve differential equations along with integral equations [114]. M-metric spaces were introduced by Asadi, Karapinar and Salimi, in [15], they are an extension of a partial metric space. Then some relationships between a partial metric and an M-metric were investigated in [16]. So, first we remind the reader of the definition of a partial metric space and an M-metric space along with some other notations.

Definition 1.1

([17, 18])

A partial metric on a nonempty set X is a function \(p_{i}:X^{2}\rightarrow [ 0,+\infty ) \) such that for all \(\lambda ,\epsilon ,z\in X\)


\(p_{i}(\lambda ,\lambda )=p_{i}(\epsilon ,\epsilon )=p_{i}(\lambda , \epsilon )\) if and only if \(\lambda =\epsilon \),


\(p_{i}(\lambda ,\lambda )\leq p_{i}(\lambda ,\epsilon )\),


\(p_{i}(\lambda ,\epsilon )=p_{i}(\epsilon ,\lambda )\),


\(p_{i}(\lambda ,\epsilon )\leq p_{i}(\lambda ,z)+p_{i}(z,\epsilon )-p_{i}(z,z)\).

A partial metric space is a pair \((X,p_{i})\) such that X is a nonempty set and \(p_{i}\) is a partial metric on X.

Notation 1.2


  1. 1.

    \(k_{\lambda ,\epsilon }:= \min \{ K(\lambda ,\lambda ),K(\epsilon , \epsilon ) \}\).

  2. 2.

    \(M_{\lambda ,\epsilon }:= \max \{ K(\lambda ,\lambda ),K(\epsilon , \epsilon ) \}\).

Definition 1.3


Let X be a nonempty set. If the function \(K:X^{2}\rightarrow [ 0,+\infty ) \) satisfies the following conditions:

  1. (1)

    \(K(\lambda ,\lambda )=K(\epsilon ,\epsilon )=K(\lambda ,\epsilon )\) if and only if \(\lambda =\epsilon \),

  2. (2)

    \(k_{\lambda ,\epsilon } \le K(\lambda ,\epsilon )\),

  3. (3)

    \(K(\lambda ,\epsilon )=K(\epsilon ,\lambda )\),

  4. (4)

    \((K(\lambda ,\epsilon )-k_{\lambda ,\epsilon })\leq (K(\lambda ,z)-k_{ \lambda ,z})+(K(z,\epsilon )-k_{z,\epsilon })\),

for all \(\lambda ,\epsilon ,z\in X\), then the pair \((X,K)\) is called an M-metric space.

Recently, Mlaiki et al. [19], developed the concept of an \(M_{b}\)-metric space which extends an M-metric space, and some fixed point theorems are established. Also, \(M_{b}\)-metric spaces are a generalization of b-metric spaces; see [2022]. Now, we remind the reader of some definitions and notations of \(M_{b}\)-metric spaces.

Notation 1.4


  1. 1.

    \(k_{{b}{\lambda ,\epsilon }}:= \min \{ K_{b}(\lambda ,\lambda ),K_{b}( \epsilon ,\epsilon ) \}\).

  2. 2.

    \(M_{{b}{\lambda ,\epsilon }}:= ma\lambda \{ K_{b}(\lambda ,\lambda ),K_{b}( \epsilon ,\epsilon ) \}\).

Definition 1.5


An \(M_{b}\)-metric on a nonempty set X is a function \(K_{b}:X^{2}\rightarrow [ 0,+\infty ) \) that satisfies the following conditions:

  1. (1)

    \(K_{b}(\lambda ,\lambda )=K_{b}(\epsilon ,\epsilon )=K_{b}(\lambda , \epsilon )\) if and only if \(\lambda =\epsilon \),

  2. (2)

    \(k_{{b}{\lambda ,\epsilon }} \le K_{b}(\lambda ,\epsilon )\),

  3. (3)

    \(K_{b}(\lambda ,\epsilon )=K_{b}(\epsilon ,\lambda )\),

  4. (4)

    there exists a real number \(s\geq 1\) such that for all \(\lambda ,\epsilon ,z\in X\) we have

    $$ \bigl(K_{b}(\lambda ,\epsilon )-k_{{b}{\lambda ,\epsilon }} \bigr)\leq s \bigl[ \bigl(K_{b}( \lambda ,z)-k_{{b}{\lambda ,z}} \bigr)+ \bigl(K_{b}(z,\epsilon )-k_{{b}{z,\epsilon }} \bigr) \bigr]-K_{b}(z,z), $$

for all \(\lambda ,\epsilon ,z\in X\). Then the pair \((X,K_{b})\) is called an \(M_{b}\)-metric space and the number s is called the coefficient of the \(M_{b}\)-metric space \((X,K_{b})\).

Note that the condition (4) given in Definition 1.5 is equivalent to the following condition:


There exists a real number \(s\geq 1\) such that for all \(\lambda ,\epsilon ,z\in X\) we have

$$ \bigl(K_{b}(\lambda ,\epsilon )-k_{{b}{\lambda ,\epsilon }} \bigr)\leq s \bigl[ \bigl(K_{b}( \lambda ,z)-k_{{b}{\lambda ,z}} \bigr)+ \bigl(K_{b}(z,\epsilon )-k_{{b}{z,\epsilon }} \bigr) \bigr], $$

for all \(\lambda ,\epsilon ,z\in X\).

Indeed, if we take \(\lambda =r\) under the condition (4) then we get

$$ K_{b}(\lambda ,\lambda )-k_{{b}{\lambda ,\lambda }}=K_{b}( \lambda , \lambda )-\min \bigl\{ K_{b}(\lambda ,\lambda ),K_{b}(\lambda , \lambda ) \bigr\} =0 $$

and so we have

$$ 0\leq s \bigl[ \bigl(K_{b}(\lambda ,\lambda )-k_{{b}{\lambda ,\lambda }} \bigr)+ \bigl(K_{b}( \lambda ,\lambda )-k_{{b\lambda }{,\lambda }} \bigr) \bigr]-K_{b}(\lambda , \lambda )\leq -K_{b}(\lambda , \lambda )\text{,} $$

for \(z=\lambda \). Therefore we get \(K_{b}(\lambda ,\lambda )=0\) for all \(\lambda \in X\) since \(K_{b}(\lambda ,\lambda )\in [ 0,+\infty ) \).

The concept of extended \(M_{b}\)-metric spaces was introduced in [23], which is a generalization of an \(M_{b}\)-metric space which also generalizes extended b-metric spaces [3]. We give basic properties of this new space and its relation with some known metric spaces.

First, we give the following notation.

Notation 1.6

  1. (1)

    \(k_{{\alpha }{\lambda ,\epsilon }}:=\min \{K_{\alpha }(\lambda , \lambda ),K_{\alpha }(\epsilon ,\epsilon )\}\).

  2. (2)

    \(M_{{\alpha }{\lambda ,\epsilon }}:=\max \{K_{\alpha }(\lambda , \lambda ),K_{\alpha }(\epsilon ,\epsilon )\}\).

Definition 1.7

Let \(\alpha :X^{2}\rightarrow {}[ 1,+\infty )\) be a function. An extended \(M_{b}\)-metric on a nonempty set X is a function \(K_{\alpha }:X^{2}\rightarrow {}[ 0,+\infty )\) satisfying the following conditions:

  1. (1)

    \(K_{\alpha }(\lambda ,\lambda )=K_{\alpha }(\epsilon ,\epsilon )=K_{ \alpha }(\lambda ,\epsilon )\) if and only if \(\lambda =\epsilon \),

  2. (2)

    \(k_{{\alpha }{\lambda ,\epsilon }} \le K_{\alpha }(\lambda ,\epsilon )\),

  3. (3)

    \(K_{\alpha }(\lambda ,\epsilon )=K_{\alpha }(\epsilon ,\lambda )\),

  4. (4)

    \((K_{\alpha }(\lambda ,\epsilon )-k_{{\alpha }{\lambda ,\epsilon }}) \leq \alpha (\lambda ,\epsilon )[(K_{\alpha }(\lambda ,z)-k_{{\alpha }{ \lambda ,z}})+(K_{\alpha }(z,\epsilon )-k_{{\alpha }{z,\epsilon }})]\),

for all \(\lambda ,\epsilon ,z\in X\). Then the pair \((X,K_{\alpha })\) is called an extended \(M_{b}\)-metric space.

We note that if \(\alpha (\lambda ,\epsilon )=s\) for \(s\geq 1\), then we get the definition of an \(M_{b}\)-metric space.

Example 1.8

Let \(X=C([a,d],\mathbb{R})\) be the set of all continuous real valued functions on \([a,b]\). We define the functions \(K_{\alpha }:X^{2}\rightarrow {}[ 0,+\infty )\) and \(\alpha :X^{2}\rightarrow {}[ 1,+\infty )\) by

$$ K_{\alpha } \bigl(\lambda (t),\epsilon (t) \bigr)=\sup _{t\in {}[ a,b]} \bigl\vert \lambda (t)-y(t) \bigr\vert ^{2} $$


$$ \alpha \bigl(\lambda (t),\epsilon (t) \bigr)= \bigl\vert \lambda (t) \bigr\vert + \bigl\vert y(t) \bigr\vert +2. $$

Then \((X,K_{\alpha })\) is an extended \(M_{b}\)-metric space with the function α.

Now we give the following proposition.

Proposition 1.9

Let\((X,K_{\alpha })\)be an extended\(M_{b}\)-metric space and\(\lambda ,\epsilon ,z\in X\). Then we have

  1. (1)

    \(M_{\alpha \lambda ,\epsilon }+k_{\alpha \lambda ,\epsilon }=K_{ \alpha }(\lambda ,\lambda )+K_{\alpha }(\epsilon ,\epsilon )\geq 0\),

  2. (2)

    \(M_{\alpha \lambda ,\epsilon }-k_{\alpha \lambda ,\epsilon }= \vert K_{\alpha }(\lambda ,\lambda )-K_{\alpha }(\epsilon ,\epsilon ) \vert \geq 0\),

  3. (3)

    \(M_{\alpha \lambda ,\epsilon }-k_{\alpha \lambda ,\epsilon }\leq \alpha (\lambda ,\epsilon ) [ ( M_{\alpha \lambda ,z}-k_{ \alpha \lambda ,z} ) + ( M_{\alpha z,\epsilon }-k_{\alpha z, \epsilon } ) ] \).

In this section, we give some topological notions on an extended \(M_{b}\)-metric space.

Definition 1.10

Let \((X,K_{\alpha })\) be an extended \(M_{b}\)-metric space. Then:

  1. (1)

    A sequence \(\{\lambda _{n}\}\) in X converges to a point λ if and only if

    $$ \lim_{n\rightarrow +\infty } \bigl(K_{\alpha }(\lambda _{n}, \lambda )-k_{{ \alpha }{\lambda _{n},\lambda }} \bigr)=0. $$
  2. (2)

    A sequence \(\{\lambda _{n}\}\) in X is said to be a \(K_{\alpha }\)-Cauchy sequence if

    $$ \lim_{n,m\rightarrow +\infty } \bigl(K_{\alpha }(\lambda _{n}, \lambda _{m})-k_{{ \alpha }{\lambda _{n},\lambda _{m}}} \bigr) $$


    $$ \lim_{n\rightarrow +\infty }(M_{{\alpha }{\lambda _{n},\lambda _{m}}}-k_{{ \alpha }{\lambda _{n},\lambda _{m}}}) $$

    exist and are finite.

  3. (3)

    An extended \(M_{b}\)-metric space is said to be \(K_{\alpha }\)-complete if every \(K_{\alpha }\)-Cauchy sequence \(\{\lambda _{n}\}\) converges to a point λ such that

    $$ \lim_{n\rightarrow +\infty } \bigl(K_{\alpha }(\lambda _{n}, \lambda )-k_{{ \alpha }{\lambda _{n},\lambda }} \bigr)=0 $$


    $$ \lim_{n\rightarrow +\infty }(M_{{\alpha }{\lambda _{n}, \lambda }}-k_{{\alpha }{\lambda _{n},\lambda }})=0. $$

Remark 1.11

If we consider Example 1.8, then it is not difficult to see that \((X,K_{\alpha })\) is a complete extended \(M_{b}\)-metric space.

Lemma 1.12

Let\((X,K_{\alpha })\)be an extended\(M_{b}\)-metric space. Then we get:

  1. (1)

    \(\{ \lambda _{n} \} \)is an\(K_{\alpha }\)-Cauchy sequence in\((X,K_{\alpha })\)if and only if\(\{ \lambda _{n} \} \)is a Cauchy sequence in\((X,K_{\alpha }^{b})\).

  2. (2)

    \((X,K_{\alpha })\)is complete if and only if\((X,K_{\alpha }^{b})\)is complete.

2 Main result

First, we start this section by proving the following theorem, which we consider our main result.

Theorem 2.1

Let\((X,K_{\alpha })\)be a complete extended\(M_{b}\)-metric space andfbe a continuous self-mapping onX. Suppose that there exists\(p \in [0,1)\)such that for all\(\lambda ,\epsilon \in X\)we have

$$ K_{\alpha }(f\lambda ,f\epsilon ) \leq p \alpha (\lambda ,\epsilon ) K_{ \alpha }(\lambda ,\epsilon ) .$$

Also, fix\(\lambda _{0} \in X\)and define the sequence\((\lambda _{n})\)defined by\(\lambda _{i} = f\lambda _{i-1}\). If

$$ \sup_{m \geq 1} \lim_{n} \alpha (\lambda _{m},\lambda _{n}) \alpha ( \lambda _{n}, \lambda _{n +1}) < \frac{1}{p}, $$

and for every\(\lambda \in X\)we have\(\{ \alpha (\lambda ,\lambda _{n})\}_{n}\)and\(\{\alpha (\lambda _{n},\lambda )\}_{n}\)are bounded. Thenfhas a fixed point onX. Moreover, if for every two fixed points\(r,s \in X\)we have\(\alpha (r,s)<\frac{1}{p}\), then the fixed point is unique.


Using the sequence as defined in the hypotheses of the theorem and (2.1)

$$\begin{aligned} K_{\alpha }(\lambda _{n}, \lambda _{n+1})&= K_{\alpha }(f\lambda _{n-1}, f\lambda _{n}) \\ & \leq p \alpha (\lambda _{n-1}, \lambda _{n})K_{\alpha }( \lambda _{n-1}, \lambda _{n}) \\ & =p \alpha (\lambda _{n-1}, \lambda _{n})K_{\alpha }(f \lambda _{n-2}, \lambda _{n-1}) \\ & \leq p^{2} \alpha (\lambda _{n-1}, \lambda _{n}) \alpha (\lambda _{n-2}, \lambda _{n-1}) K_{\alpha }(\lambda _{n-2}, \lambda _{n-1}) \\ &\quad \vdots \\ & \leq p^{n}\prod_{i=1}^{n} \alpha (\lambda _{i-1},\lambda _{i})K_{ \alpha }( \lambda _{0},\lambda _{1}). \end{aligned}$$

Now, consider \(n,m \in \mathbb{N}\) where \(m>n\). Then

$$ \begin{aligned} K_{\alpha }(\lambda _{n}, \lambda _{m})- k_{\alpha \lambda _{n}, \lambda _{m}} & \leq \alpha (\lambda _{n}, \lambda _{m}) \bigl[ \bigl(K_{\alpha }( \lambda _{n}, \lambda _{n+1})- k_{\alpha \lambda _{n}, \lambda _{n+1}} \bigr) \\ &\quad {}+ \bigl(K_{\alpha }(\lambda _{n +1}, \lambda _{m})- k_{\alpha \lambda _{n +1}, \lambda _{m}} \bigr) \bigr] \\ & \leq \alpha (\lambda _{n},\lambda _{m}) \bigl[K_{\alpha }(\lambda _{n}, \lambda _{n+1})- k_{\alpha \lambda _{n}, \lambda _{n+1}} \bigr] \\ &\quad {} +\alpha (\lambda _{n},\lambda _{m}) \alpha ( \lambda _{n+1},\lambda _{m}) \bigl[ \bigl(K_{\alpha }( \lambda _{n+1}, \lambda _{n+2})- k_{\alpha \lambda _{n+1}, \lambda _{n+2}} \bigr) \\ &\quad {}+ \bigl(K_{\alpha }(\lambda _{n +2}, \lambda _{m})- k_{\alpha \lambda _{n +2}, \lambda _{m}} \bigr) \bigr] \\ &\quad \vdots \\ & \leq \sum_{i=n}^{m-1}\prod _{j=n}^{i}\alpha (\lambda _{j}, \lambda _{m}) \bigl[K_{ \alpha }(\lambda _{i}, \lambda _{i+1})- k_{\alpha \lambda _{i}, \lambda _{i+1}} \bigr] \\ & \leq \sum_{i=n}^{m-1}\prod _{j=n}^{i}\alpha (\lambda _{j}, \lambda _{m}) \bigl[K_{ \alpha }(\lambda _{i}, \lambda _{i+1}) \bigr] \\ & \leq \sum_{i=n}^{m-1}\prod _{j=n}^{i}\alpha (\lambda _{j}, \lambda _{m})p^{i} \prod_{s=1}^{i} \alpha (\lambda _{s-1},\lambda _{s})K_{\alpha }( \lambda _{0},\lambda _{1}). \end{aligned} $$

Now, let

$$ \varGamma _{i} : = \prod_{j=n}^{i} \alpha (\lambda _{j},\lambda _{m})p^{i} \prod_{s=1}^{i}\alpha (\lambda _{s-1},\lambda _{s})K_{\alpha }( \lambda _{0},\lambda _{1}), $$


$$ \varGamma _{i + 1} : = \prod_{j=n}^{i+1} \alpha (\lambda _{j},\lambda _{m})p^{i} \prod_{s=1}^{i +1 }\alpha (\lambda _{s-1},\lambda _{s})K_{\alpha }( \lambda _{0},\lambda _{1}). $$


$$ \frac{\varGamma _{i + 1}}{\varGamma _{i }}= \alpha (\lambda _{i+1},\lambda _{m}) \alpha (\lambda _{i+1},\lambda _{i})p . $$


$$ \sup_{m \geq 1} \lim_{i} \frac{\varGamma _{i + 1}}{\varGamma _{i }}= p \sup_{m \geq 1} \lim_{i} \alpha (\lambda _{m},\lambda _{i}) \alpha ( \lambda _{i},\lambda _{i +1}) < 1, $$

which leads us to conclude that \((\lambda _{n})\) is \(K_{\alpha }\)-Cauchy sequence. Since \((X,K_{\alpha })\) is a complete extended \(M_{b}\)-metric space, we deduce that \((\lambda _{n})\) is convergent in X to some \(u \in X\). Note that \(k_{\alpha u, fu} \leq K_{\alpha }(u, fu)\) and

$$ K_{\alpha }(u, fu)- k_{\alpha u, fu} \leq \alpha (u,fu) \bigl[ \bigl(K_{\alpha }(u, \lambda _{n})- k_{\alpha u, \lambda _{n}} \bigr)+ \bigl(K_{\alpha }(\lambda _{n },fu) - k_{\alpha \lambda _{n}, fu} \bigr) \bigr]. $$

Since f is continuous and taking the limit in the above inequality we deduce that

$$ K_{\alpha }(u, fu)= k_{\alpha u, fu}. $$

Now, without loss of generality we can suppose that \(M_{\alpha u, fu}= K_{\alpha } (u, u)\).

$$ \begin{aligned} M_{\alpha \lambda _{n}, f\lambda _{n}}= K_{\alpha }(\lambda _{n}, \lambda _{n}) & \leq p \alpha (\lambda _{n-1}, \lambda _{n-1})K_{ \alpha }(\lambda _{n-1}, \lambda _{n-1}) \\ & \leq p^{2} \alpha (\lambda _{n-1}, \lambda _{n-1}) \alpha (\lambda _{n-2}, \lambda _{n-2}) K_{\alpha }(\lambda _{n-2}, \lambda _{n-2}) \\ & \quad \vdots \\ & \leq p^{n}\prod_{i=0}^{n-1} \alpha (\lambda _{i},\lambda _{i})K_{ \alpha }( \lambda _{0},\lambda _{0}). \end{aligned} $$

Taking the limit on both sides as \(n \rightarrow +\infty \) we have

$$ M_{\alpha u, fu}=0. $$

Finally, since \(K_{\alpha }(u, fu)= k_{\alpha u, fu} \leq M_{\alpha u, fu}=0\) and since \(K_{\alpha }(fu, fu)= k_{\alpha u, fu}\), it is easy to conclude that \(fu=u\). That is, f has a fixed point. Now,assume that f has two fixed points say \(s,r \in X\), that is, \(fs=s\) and \(fr=r\). Thus,

$$\begin{aligned} K_{\alpha }(s,r) &= K_{\alpha }(fs,fr) \\ & \le p \alpha (s,r) K_{\alpha }(s,r) \\ & < p.\frac{1}{p}K_{\alpha }(s,r) \\ &=K_{\alpha }(s,r), \end{aligned}$$

which implies that \(K_{\alpha }(s,r)=0\), therefore \(K_{\alpha }(s,r)=k_{\alpha _{r,s}}=0\). Now, we may assume that \(M_{\alpha _{r,s}}=K_{\alpha }(s,s)\), hence \(K_{\alpha }(s,s)=K_{\alpha }(fs,fs)\le p \alpha (s,s) K_{\alpha }(s,s)< K_{ \alpha }(s,s)\). Hence, \(K_{\alpha }(s,s)=0\), which leads us to conclude that

$$ K_{\alpha }(s,r)=k_{\alpha _{r,s}}=M_{\alpha _{r,s}}=0 $$

and that \(r=s\) as required. □

Example 2.2

Let \(X=[0,1]\) and let f: XX defined by

$$ f(\lambda )= \frac{\lambda }{2 + 2\lambda }. $$

Then f has a unique fixed point.


For all \(\lambda ,\epsilon \in X\), let \(K_{\alpha }(\lambda ,\epsilon )= \frac{(\lambda +\epsilon )^{2}}{2}\) and \(\alpha (\lambda ,\epsilon )= 1+\lambda +\epsilon \). An easy argument shows that \((X, K_{\alpha } )\) is a \(K_{\alpha }\)-complete extended \(M_{b}\)-metric space. Also we have

$$\begin{aligned} K_{\alpha }(f\lambda ,f\epsilon )&= \frac{(f\lambda + f\epsilon )^{2}}{2 } = \frac{(\frac{\lambda }{2 + 2\lambda } + \frac{\epsilon }{2 + 2\epsilon })^{2}}{2 } \\ &\le \frac{1}{4} \frac{(\lambda +\epsilon )^{2}}{2} \\ &\le \frac{1}{4}(1 + \lambda + \epsilon ) \frac{(\lambda +\epsilon )^{2}}{2} \\ &= \frac{1}{4} \alpha (\lambda ,\epsilon ) K_{\alpha }(\lambda , \epsilon ). \end{aligned}$$


$$ K_{\alpha }(f\lambda ,f\epsilon )\le p \alpha (\lambda ,\epsilon ) K_{ \alpha }(\lambda ,\epsilon ),\quad \text{where } p= \frac{1}{4}. $$

Now, by induction it is not difficult to deduce that

$$ \lambda _{n}= f^{n}(\lambda )= \frac{\lambda }{2^{n} + (\sum_{k=1}^{n}2^{k})\lambda } $$

for all \(n \in \mathbb{N}\). Thus,

$$ \lim_{n\rightarrow +\infty } \alpha (\lambda ,\lambda _{n})=\lim _{n \rightarrow +\infty } \alpha (\lambda _{n},\lambda ) = 1+\lambda . $$

On the other hand,

$$\begin{aligned} \sup_{m\geq 1}\lim_{n \rightarrow +\infty }\alpha (\lambda _{n}, \lambda _{m})\alpha (\lambda _{n+1}, \lambda _{n}) = &\sup_{m\geq 1} \biggl(1+ \frac{\lambda }{2^{m} + (\sum_{k=1}^{m}2^{k})\lambda } \biggr) \\ =& 1 + \frac{\lambda }{2 + 2\lambda } \\ \le &2< 4=\frac{1}{p}. \end{aligned}$$

It is not difficult to check that f: \((X, K_{\alpha })\)\((X, K_{\alpha })\) is continuous. Finally, note that f satisfies all the hypotheses of Theorem 2.1. Therefore, f has a unique fixed point in X. □

Theorem 2.3

Let\((X,K_{\alpha })\)be a complete extended\(M_{b}\)-metric space, and letfbe a continuous self-mapping onX. Assume that there exist\(a,b \in [0, + \infty )\)with

$$ \lim_{n} \frac{a\alpha (\lambda _{n},\lambda _{n -1})}{1-b\alpha (\lambda _{n},\lambda _{n +1})} < 1 $$


$$ \alpha (\lambda _{n},\lambda _{n +1}) < \frac{1}{a+b},\quad \textit{where } \lambda _{n}= f^{n} \lambda _{0}. $$

If\(K_{\alpha }(f\lambda ,fy)\le a \alpha (\lambda ,f\lambda K_{\alpha }( \lambda ,f\lambda + b \alpha (\epsilon ,fy) K_{\alpha }(\epsilon ,fy)\), thenfhas a unique fixed point inX.


Let \(\lambda _{0}\in X\) and define the sequence \(\{\lambda _{n}\}\) as follows:

$$ \lambda _{1}=f\lambda _{0},\qquad \lambda _{2}=f \lambda _{1}=f^{2}\lambda _{0}, \qquad \ldots ,\qquad \lambda _{n}=f\lambda _{n-1}=f^{n}\lambda _{0},\qquad \ldots. $$

We prove first that

$$ K_{\alpha }(\lambda _{n},\lambda _{n+1}) \leq a^{n}\prod_{i=1}^{n} \biggl[ \frac{\alpha (\lambda _{i},\lambda _{i -1})}{1-b\alpha (\lambda _{i},\lambda _{i +1})} \biggr]K_{ \alpha }(\lambda _{0},\lambda _{1}). $$

To this end, let \(n \in \mathbb{N}^{\star }\), then

$$\begin{aligned} K_{\alpha }(\lambda _{n},\lambda _{n+1})&= K_{\alpha }(f\lambda _{n-1},f \lambda _{n}) \\ &\le a \alpha (\lambda _{n-1},f\lambda _{n - 1}) K_{\alpha }(\lambda _{n-1},f \lambda _{n-1})+ b \alpha (\lambda _{n},f\lambda _{n}) K_{\alpha }( \lambda _{n},f\lambda _{n}) \\ &= a \alpha (\lambda _{n-1},\lambda _{n}) K_{\alpha }(\lambda _{n-1}, \lambda _{n})+ b \alpha (\lambda _{n},\lambda _{n+1}) K_{\alpha }( \lambda _{n},\lambda _{n+ 1}). \end{aligned}$$


$$\begin{aligned} K_{\alpha }(\lambda _{n},\lambda _{n+1})& \leq a \frac{\alpha (\lambda _{n},\lambda _{n -1})}{1-b\alpha (\lambda _{n},\lambda _{n +1})}K_{ \alpha }(\lambda _{n},\lambda _{n-1}) \\ & = a \frac{\alpha (\lambda _{n},\lambda _{n -1})}{1-b\alpha (\lambda _{n},\lambda _{n+1})}K_{ \alpha }(f\lambda _{n - 1},f \lambda _{n-2}) \\ &\leq a^{2} \frac{\alpha (\lambda _{n},\lambda _{n -1}\alpha (\lambda _{n-1},\lambda _{n -2})}{(1-b\alpha (\lambda _{n},\lambda _{n +1}))(1-b\alpha (\lambda _{n-1},\lambda _{n}))}K_{ \alpha }(\lambda _{n-1},\lambda _{n-2}) \\ &\le \cdots \\ & \le a^{n}\prod_{i=1}^{n} \biggl[ \frac{\alpha (\lambda _{i},\lambda _{i -1})}{1-b\alpha (\lambda _{i},\lambda _{i +1})} \biggr]K_{ \alpha }(\lambda _{0}, \lambda _{1}). \end{aligned}$$

Since \(\lim_{n} \frac{a\alpha (\lambda _{n},\lambda _{n -1})}{1-b\alpha (\lambda _{n},\lambda _{n +1})} < 1\), it follows from the ratio test that

$$ \sum_{n=1}^{\infty }a^{n}\prod _{i=1}^{n} \frac{\alpha (\lambda _{i},\lambda _{i -1})}{1-b\alpha (\lambda _{i},\lambda _{i +1})} $$

converges, which implies that \(K_{\alpha }(\lambda _{n},\lambda _{n+1}) \text{converges to $0$} \).

Next, let \(n, m \in \mathbb{N}^{\star }\), then

$$\begin{aligned} K_{\alpha }(\lambda _{n},\lambda _{m})&= K_{\alpha }(f\lambda _{n-1},f \lambda _{m-1}) \\ & \leq a \alpha (\lambda _{n-1},\lambda _{n}) K_{\alpha }(\lambda _{n-1}, \lambda _{n})+ b \alpha (\lambda _{m-1},f\lambda _{m}) K_{\alpha }( \lambda _{m-1},\lambda _{m}). \end{aligned}$$

By the above inequality, we deduce that \(K_{\alpha }(\lambda _{n},\lambda _{m}) \text{converges to $0$} \). Since

$$ k_{\alpha \lambda _{m},\lambda _{n}}:= \min \bigl(K_{\alpha }(\lambda _{n}, \lambda _{n}), K_{\alpha }(\lambda _{m},\lambda _{m}) \bigr) \leq K_{ \alpha }(\lambda _{n}, \lambda _{m}), $$

we conclude that

$$ \lim_{n,m \rightarrow + \infty } \bigl(K_{\alpha }(\lambda _{n},\lambda _{m})- k_{\alpha \lambda _{m},\lambda _{n}} \bigr) = 0. $$

Now, without loss of generality we may assume that

$$ M_{\alpha \lambda _{m},\lambda _{n}}:= \max \bigl(K_{\alpha }(\lambda _{n}, \lambda _{n}), K_{\alpha }(\lambda _{m},\lambda _{m}) \bigr)= K_{\alpha }( \lambda _{n},\lambda _{n}). $$

Hence, we obtain

$$\begin{aligned} M_{\alpha \lambda _{m},\lambda _{n}}-k_{\alpha \lambda _{m},\lambda _{n}} & \leq M_{\alpha \lambda _{m},\lambda _{n}} \\ & = K_{\alpha }(\lambda _{n},\lambda _{n}) \\ &\leq (a+b)\alpha (\lambda _{n-1},\lambda _{n})K_{\alpha }( \lambda _{n-1}, \lambda _{n}) . \end{aligned}$$

Taking the limit of the above inequality as \(n \rightarrow +\infty \) we deduce that

$$ \lim_{n,m \rightarrow + \infty } (M_{\alpha \lambda _{m},\lambda _{n}}-k_{ \alpha \lambda _{m},\lambda _{n}}) = 0. $$

Thus, the sequence \(\{\lambda _{n}\}\) is a \(K_{\alpha }\)-Cauchy sequence. Since \((X, K_{\alpha })\) is a \(K_{\alpha }\)-complete extended b-metric space, we conclude that \(\{\lambda _{n}\}\) converges to some \(\omega \in X\), and so \(\{f\lambda _{n} = \lambda _{n+1}\}\) converges to \(\omega \in X\). On the other hand, by the hypotheses of the theorem (\(f: (X, K_{\alpha })\rightarrow (X, K_{\alpha })\) is continuous) it is not difficult to conclude that \(\{f\lambda _{n}\}\) converges to \(f\omega \in X\). From Lemma 3.3 in [23], we have

$$ K_{\alpha }(\omega ,f\omega )- k_{\alpha \omega ,f\omega } = 0. $$


$$\begin{aligned} K_{\alpha }(\omega ,f\omega )&= K_{\alpha }( f\omega ,f\omega ) \\ & \leq a \alpha (\omega ,f\omega ) K_{\alpha }(\omega ,f\omega )+ b \alpha (\omega ,f\omega ) K_{\alpha }(\omega ,f\omega ) \\ &=(a+b)\alpha (\omega ,f\omega ) K_{\alpha }(\omega ,f\omega ) \\ & < K_{\alpha }(\omega ,f\omega ) . \end{aligned}$$


$$ K_{\alpha }(\omega ,f\omega )= K_{\alpha }( f\omega ,f\omega )=0. $$

Similarly to the above we have

$$ K_{\alpha } \bigl(f\omega ,f^{2}\omega \bigr)= K_{\alpha } \bigl( f^{2}\omega ,f^{2} \omega \bigr)=0. $$

Since \((X, K_{\alpha })\) is an extended b-metric space, it follows that

$$ ff\omega =f\omega . $$

We deduce that \(\omega '= f\omega \) is a fixed point of f. Finally, to show uniqueness assume that there exists another fixed point of f, say u. By the contractive property of f we have

$$\begin{aligned} K_{\alpha } \bigl(u,\omega ' \bigr)&=K_{\alpha } \bigl(fu,f\omega ' \bigr) \\ & \leq a \alpha (u,fu) K_{\alpha }(u,fu)+ b \alpha \bigl(\omega ',f\omega ' \bigr) K_{\alpha } \bigl(\omega ',f\omega ' \bigr). \end{aligned}$$

From (2.2) we get

$$ K_{\alpha } \bigl(u,\omega ' \bigr) \leq a \alpha (u,fu) K_{\alpha }(u,fu). $$


$$\begin{aligned} K_{\alpha } \bigl(u,\omega ' \bigr) & \leq a \alpha (u,fu) K_{\alpha }(u,fu) \\ & =a \alpha (u,fu) K_{\alpha }(fu,fu) \\ & \leq a \alpha (u,fu) \bigl[(a+b)\alpha (u,fu) \bigr] K_{\alpha }(u,fu) \\ &\le \cdots \\ & \le a \alpha (u,fu) \bigl[(a+b)\alpha (u,fu) \bigr]^{n} K_{\alpha }(u,fu). \end{aligned}$$

Since \((a+b)\alpha (u,fu) = (a+b)\alpha (fu,f^{2}u)< 1 \), it follows that \([(a+b)\alpha (u,fu)]^{n}\) converges to 0. So \(K_{\alpha }(u,\omega ')= K_{\alpha }(u,u)=0\). By (2.2) we have

$$ K_{\alpha } \bigl(u,\omega ' \bigr)= K_{\alpha }(u,u)= K_{\alpha } \bigl(\omega ', \omega ' \bigr)= 0. $$

Thus, f has a unique fixed point as required. □

3 Application

Consider the set \(X= C([0,1], \mathbb{R})\) and the following Fredholm type integral equation:

$$ x'(t)= \int _{0}^{1}\mathbb{G} \bigl(t,s, x'(t) \bigr)\,ds, \quad \text{for } t,s \in [0,1] ,$$

where \(\mathbb{G}(t,s,x'(t))\) is a continuous function from \([0,1]^{2}\) into \(\mathbb{R}\). Now, define

$$ \begin{aligned} K_{\alpha }:{} &X \times X \longrightarrow \mathbb{R} \\ & (x,y) \mapsto \sup_{t \in [0,1]} \biggl(\frac{ \vert x'(t) \vert + \vert y(t) \vert }{2} \biggr). \end{aligned} $$

Note that \((X, K_{\alpha })\) is a \(K_{\alpha }\)-complete extended \(M_{b}\)-metric space, where

$$ \alpha (x,y)=1 + \sup_{t \in [0,1]} \bigl( \bigl\vert x'(t) \bigr\vert \bigl\vert y(t) \bigr\vert \bigr). $$

Theorem 3.1

Assume that for all\(x,y \in X\):

  1. (1)

    \(|\mathbb{G}(t,s,x'(t))| + |\mathbb{G}(t,s,y(t))| \leq p (1 + \sup_{t \in [0,1]}\{|x'(t)||y(t)|\}) (|x'(t)| +|y(t)|)\), for some\(p \in [0, \frac{1}{(1 + \sup_{t,s}|\mathbb{G}(t,s, x'(t))||\mathbb{G}(t,s, y(t))|)^{2}})\).

  2. (2)

    \(\mathbb{G}(t,s, \int _{0}^{1}\mathbb{G}(t,s, x'(t))\,ds ) < \mathbb{G}(t,s, x'(t) ) \)for allt, s.

Then the above integral equation has a unique solution.


Let \(f: X \longrightarrow X\) be defined by \(fx'(t) = \int _{0}^{1}\mathbb{G}(t,s, x'(t))\,ds\), then

$$ K_{\alpha }(fx,fy)= \sup_{t \in [0,1]}\biggl(\frac{|fx'(t)|+|fy(t)|}{2}\biggr). $$

Now we have

$$ \begin{aligned} \frac{ \vert fx'(t) \vert + \vert fy(t) \vert }{2} & = \frac{ \vert \int _{0}^{1}\mathbb{G}(t,s, x'(t))\,ds \vert + \vert \int _{0}^{1}\mathbb{G}(t,s, y(t))\,ds \vert }{2} \\ & \leq \frac{\int _{0}^{1} \vert \mathbb{G}(t,s, x'(t)) \vert \,ds+\int _{0}^{1} \vert \mathbb{G}(t,s, y(t)) \vert \,ds}{2} \\ & = \frac{\int _{0}^{1}( \vert \mathbb{G}(t,s, x'(t)) \vert + \vert \mathbb{G}(t,s, y(t)) \vert )\,ds}{2} \\ & \leq \frac{\int _{0}^{1}p(1 + \sup_{t \in [0,1]}\{ \vert x'(t) \vert \vert y(t) \vert \})( \vert x'(t) \vert + \vert y(t) \vert )\,ds}{2} \\ & \leq p \alpha (x,y)K_{\alpha }(x,y). \end{aligned} $$

Consequently, \(K_{\alpha }(fx,fy) \leq \alpha (x,y)K_{\alpha }(x,y)\). On the other hand, let \(n \in \mathbb{N}^{\star }\) and \(x \in X\), then

$$ \begin{aligned} \bigl(f^{n}x \bigr) (t) &= f \bigl(f^{n-1}x'(t) \bigr) = \int _{0}^{1}\mathbb{G} \bigl(t,s, f^{n-1}x'(t) \bigr)\,ds \\ & = \int _{0}^{1}\mathbb{G} \bigl(t,s, f \bigl(f^{n-2}x \bigr) (t) \bigr)\,ds \\ & = \int _{0}^{1}\mathbb{G} \biggl(t,s, \int _{0}^{1}\mathbb{G} \bigl(t,s, \bigl(f^{n-2}x'(t) \bigr) \bigr) \biggr)\,ds \\ & < \int _{0}^{1}\mathbb{G} \bigl(t,s, \bigl(f^{n-2}x'(t) \bigr) \bigr)\,ds= \bigl(f^{n-1}x'(t) \bigr). \end{aligned}$$

Thus, for all \(t \in [0,1]\) we find that \((f^{n}x'(t))_{n}\) is strictly decreasing and a sequence bounded below, and so it converges to some l. Since \((f_{n})_{n}\) is a monotone sequence, it follows from the Dini theorem that \(\sup_{t}|f^{n}x'(t)|\) converges to some \(l' \leq \sup_{t,s}|\mathbb{G}(t,s, x'(t))|\). Observe that \(\alpha (f^{n}x, f^{m}(x))= 1+ \sup_{t}|f^{n}x'(t)| |f^{m}x'(t)|\) converges to \(1+l^{\prime 2} \leq 1+ (\sup_{t,s}|\mathbb{G}(t,s, x'(t))|)^{2}\). So

$$ \sup_{m} \lim_{n} \alpha \bigl(f^{n}x, f^{m}(x) \bigr)\alpha \bigl(f^{n}x, f^{n+1}x'(t) \bigr) \leq \Bigl(1+ \Bigl(\sup _{t,s} \bigl\vert \mathbb{G} \bigl(t,s, x'(t) \bigr) \bigr\vert \Bigr)^{2} \Bigr)^{2} < \frac{1}{p}. $$

Now, note that all the hypotheses of Theorem 2.1, are satisfied and thus Eq. (3.1) has a unique solution. □

4 Conclusion

In closing, note that in this manuscript we proved fixed point results for mappings that satisfy more general contractions, which generalizes many results obtained for mapping satisfying Banach contraction and by taking \(\alpha (\lambda ,\epsilon )= 1\) for all \(\lambda , \epsilon \in X\) in Theorem 2.1.


  1. Abdeljawad, T., Ullah, K., Ahmad, J., Mlaiki, N.: Iterative approximation of endpoints for multivalued mappings in Banach spaces. J. Funct. Spaces 2020, Article ID 2179059 (2020).

    Article  MathSciNet  MATH  Google Scholar 

  2. Mitrović, Z.D., Aydi, H., Mlaiki, N., Gardaševi-Filipović, M., Kukić, K., Radenović, S., de la Sen, M.: Some new observations and results for convex contractions of Istratescu’s type. Symmetry 11(12), 1457 (2019).

    Article  Google Scholar 

  3. Mukheimer, A., Mlaiki, N., Abodayeh, K., Shatanawi, W.: New theorems on extended b-metric spaces under new contractions. Nonlinear Anal., Model. Control 24(6), 870–883 (2019)

    MathSciNet  MATH  Google Scholar 

  4. Işık, H., Moeini, B., Aydi, H., Mlaiki, N.: Fixed points of subadditive maps with an application to a system of Volterra–Fredholm type integrodifferential equations. Math. Probl. Eng. 2019, Article ID 6925891 (2019).

    Article  MathSciNet  Google Scholar 

  5. Rashid, T., Khan, Q.H., Mlaiki, N., Aydi, H.: Some noncontractive maps on incomplete metric spaces have also fixed points. J. Funct. Spaces 2019, Article ID 2038757 (2019)

    MathSciNet  MATH  Google Scholar 

  6. Lakzian, H., Barootkoob, S., Mlaiki, N., Aydi, H., De la Sen, M.: On generalized \((\alpha , \phi , M_{X})\)-contractions with w-distances and an application to nonlinear Fredholm integral equations. Symmetry 11(8), 982 (2019)

    Article  Google Scholar 

  7. Todorčević, V.: Subharmonic behavior and quasiconformal mappings. Anal. Math. Phys. 9(3), 1211–1225 (2019)

    Article  MathSciNet  Google Scholar 

  8. Manojlović, V.: On conformally invariant extremal problems. Appl. Anal. Discrete Math. 3(1), 97–119 (2009)

    Article  MathSciNet  Google Scholar 

  9. Vujaković, J., Mitrović, S., Pavlović, M., Radenović, S.: On recent results concerning F-contraction in generalized metric spaces. Mathematics 8, 767 (2020).

    Article  Google Scholar 

  10. Ćirić, L.: Some Recent Results in Metrical Fixed Point Theory. University of Belgrade, Beograd (2003)

    Google Scholar 

  11. Kirk, W., Shahzad, N.: Fixed Point Theory in Distance Spaces. Springer, Cham (2014)

    Book  Google Scholar 

  12. Alghamdi, M., Gülyaz-Özyurt, S., Karapınar, E.: A note on extended Z-contraction. Mathematics 8(2), 195 (2020).

    Article  Google Scholar 

  13. Abdeljawad, T., Karapınar, E., Panda, S.K., Mlaiki, N.: Solutions of boundary value problems on extended-Branciari b-distance. J. Inequal. Appl. 2020(1), 103 (2020).

    Article  MathSciNet  Google Scholar 

  14. Panda, S.K., Karapınar, E., Atangana, A.: A numerical schemes and comparisons for fixed point results with applications to the solutions of Volterra integral equations in dislocated extended b-metric space. Alex. Eng. J. 59, 815–827 (2020).

    Article  Google Scholar 

  15. Asadi, M., Karapınar, E., Salimi, P.: New extension of p-metric spaces with some fixed point results on M-metric spaces. J. Inequal. Appl. 2014, 18 (2014)

    Article  MathSciNet  Google Scholar 

  16. Abodayeh, K., Mlaiki, N., Abdeljawad, T., Shatanawi, W.: Relations between partial metric spaces and M-metric spaces, Caristi Kirk’s theorem in M-metric type spaces. J. Math. Anal. 7(3), 1–12 (2016)

    MathSciNet  MATH  Google Scholar 

  17. Matthews, S.: Partial metric topology. Ann. N.Y. Acad. Sci. 728, 183–197 (1994)

    Article  MathSciNet  Google Scholar 

  18. Shatanawi, W., Postolache, M.: Coincidence and fixed point results for generalized weak contractions in the sense of Berinde on partial metric spaces. Fixed Point Theory Appl. 2013, Article ID 54 (2013)

    Article  MathSciNet  Google Scholar 

  19. Mlaiki, N., Zarrad, A., Souayah, N., Mukheimer, A., Abdeljawed, T.: Fixed point theorems in \(M_{b}\)-metric spaces. J. Math. Anal. 7, 1–9 (2016)

    MathSciNet  MATH  Google Scholar 

  20. Qawaqneh, H., Noorani, M.S.M., Shatanawi, W., Aydi, H., Alsamir, H.: Fixed point results for multi-valued contractions in b-metric spaces and an application. Mathematics 7(2), 132 (2019)

    Article  Google Scholar 

  21. Qawaqneh, H., Noorani, M.S.M., Shatanawi, W.: Fixed point theorems for \((\alpha , k, \theta )\)-contractive multi-valued mapping in b-metric space and applications. Int. J. Math. Comput. Sci. 14(1), 263–283 (2019)

    MathSciNet  MATH  Google Scholar 

  22. Shatanawi, W., Abodayeh, K., Mukhemer, A.: Some fixed point theorems in extended b-metric spaces. UPB Sci. Bull., Ser. A, Appl. Math. Phys. 80(4), 71–78 (2018)

    MathSciNet  MATH  Google Scholar 

  23. Mlaiki, N., Ozgür, N.Y., Mukheimer, A., Taş, N.: A new extension of the \(M_{b}\)-metric spaces. J. Math. Anal. 9(2), 118–133 (2018)

    MathSciNet  Google Scholar 

Download references


The first and thrid authors would like to thank Prince Sultan University for funding this work through research group Nonlinear Analysis Methods in Applied Mathematics (NAMAM) group number RG-DES-2017-01-17.

Availability of data and materials

Not applicable.


Not applicable.

Author information

Authors and Affiliations



All the authors have contributed equally in all parts. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Thabet Abdeljawad.

Ethics declarations

Competing interests

The authors declare to have no conflict of interest.

Additional information


Not applicable.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit

Reprints and permissions

About this article

Check for updates. Verify currency and authenticity via CrossMark

Cite this article

Mlaiki, N., Hajji, M. & Abdeljawad, T. Fredholm type integral equation in extended \(M_{b}\)-metric spaces. Adv Differ Equ 2020, 289 (2020).

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: